Improvement of fuel properties for palm oil methyl ester (POME) biodiesel blends using organic germanium as additives - M. F., Othman; Abdul Adam, Abdullah; K., Kamal; Syuhaida, Asri; Zulkifli, Azmi; R., Mamat (IOP Publishing, 2019)
Biodiesel is a clean-burning alternative fuel but it is susceptible to lower calorific value due to autoxidation in the presence of oxygen, which hinders its widespread use. Organic germanium Ge-132 is a prospective solution to this problem. It is expected that Ge-132 may affect the energy content of blending biodiesel. This paper presents an experimental investigation of the effect of Ge-132 addition to palm biodiesel on physicochemical properties. Three concentrations including 5ppm, 8ppm and 10ppm added to BD20 to study their fuel physical characteristics effect. The fuel and additive was blend by using ultrasonic emulsifier for 2 minutes before experiment. The results show that BD20 with additive Ge-132 produced 0.48%– 1.07% higher density and 0.7%–1.7% higher kinematic viscosity and 0.09%-0.6% higher calorific value compared to BD20 without the additive. The higher calorific value blending biodiesel attribute by the carbon content on Ge-132. Compared to BD20, the blended biodiesel with additive Ge-132 produce higher density, kinematic viscosity and calorific value which attribute the increase the performance and better fuel consumption.